2021
DOI: 10.1007/s40843-020-1579-7
|View full text |Cite
|
Sign up to set email alerts
|

Pd single-atom monolithic catalyst: Functional 3D structure and unique chemical selectivity in hydrogenation reaction

Abstract: Regulating the selectivity of catalysts in selective hydrogenation reactions at the atomic level is highly desirable but remains a grand challenge. Here we report a simple and practical strategy to synthesize a monolithic single-atom catalyst (SAC) with isolated Pd atoms supported on bulk nitrogen-doped carbon foams (Pd-SAs/CNF). Moreover, we demonstrate that the single-atom Pd sites with unique electronic structure endow Pd-SAs/CNF with an isolated site effect, leading to excellent activity and selectivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…This can be attributed to the linear combination of CO on Pd species with distinct electron deficiency in Pd–Zn dual sites and individual Pd sites in comparison with Pd–Pd sites. The varying decrease in electron density of Pd discloses the slight electron transfer from Pd to Zn atoms in Pd–Zn dual sites and the strong electron transfer from Pd to the carrier in individual Pd sites 56 59 .…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the linear combination of CO on Pd species with distinct electron deficiency in Pd–Zn dual sites and individual Pd sites in comparison with Pd–Pd sites. The varying decrease in electron density of Pd discloses the slight electron transfer from Pd to Zn atoms in Pd–Zn dual sites and the strong electron transfer from Pd to the carrier in individual Pd sites 56 59 .…”
Section: Resultsmentioning
confidence: 99%
“…[34,35] To realize the practical use of the single atomic site catalysts, several problems are needed to be considered, such as regulating the catalytic efficiency of metallic center, regulating the conductivity of basement and so on. [36][37][38][39][40][41][42] The interaction between metallic center and basement has also been noticed for a long time. [43][44][45] However, it hasnt been clearly figured out, which may act as an effective strategy to overcome the existing barriers of HER.…”
mentioning
confidence: 98%
“…Previous work showed that most carbon-supported SACs with abundant nitrogen-doped are stable activated single-metal ions to form the homogeneous microcosmic structure of M-N x -C y . The universal methods for synthesizing carbon-supported SACs include molecular skeleton encapsulation, [34][35][36][37][38] impregnation and pyrolysis, [39][40][41] coordination regulation, [42][43][44] and thermal dispersion.…”
Section: Carbon-supported Sacsmentioning
confidence: 99%